Association between self-reported hypertension onset age and electrocardiographic left ventricular hypertrophy - Arttu O. Lehtonen; Karri Suvila; Antti M. Jula; Teemu J. Niiranen (SPRINGERNATURE, 2025)
Objectively defined early-onset hypertension, based on repeated blood pressure measurements, is associated with greater odds of organ damage and cardiovascular mortality than late-onset hypertension. In this study we examined the association between two factors that are easily available in primary care, self-reported hypertension onset age and electrocardiographic left ventricular hypertrophy (ECG-LVH), in a nationwide population sample of 2864 Finns aged >= 50 years. We observed that, in contrast to prior findings, the odds of ECG-LVH were similar between self-reported hypertension onset age groups, and thus self-reported early-onset hypertension does not seem to associate with ECG-LVH more strongly than simple presence of hypertension.